Several social factors that influence economic growth in Malaysia / Gelbino Morris - Morris, Gelbino (2014)
Economic of a country can be developed by using many factors. In this study, we used the education (tertiary education), health (life expectancy), and unemployment (unemployment rate) effect towards the economic growth. The data used is in time series where we get obtained from the World Bank Data and also the Department Statistic of Malaysia which is from year 1982 to 2011. The result is the education and health has positive relationship with economic growth while the unemployment has negative relationship with economic growth. But for the case of significant, only the education and the unemployment that is significant in explaining the economic growth. Method used in this study is the Ordinary Least Square, Durbin-Watson test, and lastly the correlation coefficient effect.